Compatibility and stability studies involving polymers used in fused deposition modeling 3D printing of medicines - Ihatanderson A. Silva; Ana Luiza Lima; Tais Gratieri; Guilherme M. Gelfuso; Livia L. Sa-Barreto; Marcilio Cunha-Filho (Elsevier, 2022)
One of the challenges in developing three-dimensional printed medicines is related to their stability due to the manufacturing conditions involving high temperatures. This work proposed a new protocol for preformulation studies simulating thermal processing and aging of the printed medicines, tested regarding their morphology and thermal, crystallographic, and spectroscopic profiles. Generally, despite the strong drug-polymer interactions observed, the chemical stability of the model drugs was preserved under such conditions. In fact, in the metoprolol and Soluplus® composition, the drug's solubilization in the polymer produced a delay in the drug decomposition, suggesting a protective effect of the matrix. Paracetamol and polyvinyl alcohol mixture, in turn, showed unmistakable signs of thermal instability and chemical decomposition, in addition to physical changes. In the presented context, establishing protocols that simulate processing and storage conditions may be decisive for obtaining stable pharmaceutical dosage forms using three-dimensional printing technology.